Regional Level of Conflic Dynamics in the South Caucasus : Russia's Policies Towards the Ethno-Territorial Conflicts (1991-2008) - Abushov, Kavus (Westfälischen Wilhems-Univeristät, 2010)
The disintegration of the Soviet Union in 1991 produced both external and internal implications for the international system. Among other things, it put an end to the Mutually Assured Destruction System, the East-West conflict and a division of the world into two political and ideological camps. Internally, fifteen new states emerged out of its disintegration, putting an end to their 200 year old common existence within the Russian Empire and the Soviet Union. This process however also produced challenges and difficulties, part of which had been inherited from the late Soviet period. The new states faced difficulties as state-building, corruption, immaturity of political elites and power struggles, economic decline, dangerous ethnic nationalisms and ethno-territorial conflicts. As a result, within a short period of time the post-Soviet space turned into an arena of global attention in the form of great power rivalry, conflict stalemate and political disturbances. Nowhere else in the post-Soviet space are the above-mentioned phenomena as conspicuous as in the South Caucasus. The collapse of the Soviet Union on the one hand pushed the three societies to establish new institutions, and pursue state-building projects, but on the other hand, to tackle the ethnic and political grievances left from the late Soviet era, for which their respective elites had no maturity or experience.1 Despite 70 years of co-existence, relations between the title nations and minorities suddenly deteriorated to an unprecedented level, culminating in brutal wars and ultimately ending in secessionism. Ethnic and political relations aggravated on the one hand between Baku and the largely Armenian populated enclave of Mountainous Karabakh in Azerbaijan, and on the other hand between Tbilisi and its autonomous regions in late 1980s, becoming an important factor of instability in the region. All three regions declared their independence from their parent states on the eve of the collapse of the Soviet Union and ever since have existed as de facto states in the region. The picture became more complicated when all three conflicts developed regional dynamics, to be linked to the interests and policies of the regional hegemon-Russia. Russia has declared the South Caucasus a region of its strategic interests. It has been the primary peacekeeper and peace-maker in all three conflicts, it has enjoyed political and military presence in the region and has been sensitive to any development there. Meanwhile, Russia has also been accused by the conflict parties of contributing to the continuing conflict dynamics in the region, and of destabilising the region for its own ends. The Russian authorities have naturalised the residents of Abkhazia and South Ossetia, recognised both egions’ independence, but have come to hold a more neutral stance towards the Mountainous Karabakh conflict. Russia has seemingly become interested in the survival of the post violence status-quo in the region, which is a challenge to the state and nation-building process of Georgia. Policymakers in the Kremlin explain their policies as aimed at guaranteeing stability in the region and stress their domestic security interests here, whereas the reality is, Russia is intent on guaranteeing the survival of the secessionist authorities for its own ends. The central aim of this thesis is to examine Russia’s policies towards the three conflicts in the region in the context of its strategic interests in the South Caucasus. In particular it seeks to answer the following research questions: To what extent does Russia support the secessionist regions in the South Caucasus and what are the incentives of its policies. What are the strategic interests that act as the driving force behind its policies? The exploration of Russia’s engagement in all three conflicts also sheds light on a number of correlations as Russia’s bilateral relations with the states in the region, its engagement with the West, as well as its capacity and leeway to resolve the conflicts. In particular, an underlying question is the impact of Russia’s bilateral relations with the South Caucasus states on its policies towards the conflicts. Further, it is assessed whether Russia’s policies of engagement in the secessionist regions are aimed at retaining the status-quo for power-political ends or its domestic security concerns in the North Caucasus. This raises the question over Russia’s capacity to resolve the conflicts. It explores the significance of the South Caucasus to Russia’s domestic security and power-political interests and defines which one acts as the causal variable in its engagement in the region. It elucidates the nature of Russia’s great power status and hegemony in the post-soviet space and their correlation with its policies towards the conflicts. The thesis further assesses if international relations theory can be useful in explaining Russia’s policies towards the three conflicts. It utilises the regional security complex theory to explain the security interconnectedness in the Caucasus. Further, it assesses to what extent various accounts of the realist tradition of state behavior can explain the phenomenon raised in this thesis. Exploring the nature of Russian hegemony in the CIS and its overall position, a concept of relevant power is suggested. The study also sheds light (albeit limited) on the importance of geopolitics as a discourse in Russian foreign policy. Although some scholars have written on Russia’s policies towards the South Caucasus region, this study is original in a way that it examines systematically Russia’s behavior towards the conflicts in its periphery for the whole post-Soviet period.
Keywords: Caucasus, South -- Relations -- Russia (Federation).; Caucasus, South -- Ethnic relations.; Caucasus, South -- History